Determinan Potensi Risiko Stunting: Sistematis Literatur Review - Wiyono, Sugeng; Sumantri, Arif (JGK: Jurnal Gizi dan Kesehatan, 2025)
Stunting is a significant health issue affecting the world today, particularly in developing countries. The Southeast Asian region accounts for more than a quarter of all stunted children worldwide. In addition to impacting child development, mortality, and morbidity will also affect the economy and productivity of countries in the future. This scoping review aims to systematically map the research conducted in this area and identify existing knowledge gaps related to risk factors for stunting. The scoping review was conducted using three PubMed databases, the keywords used were "Children", "Risk Factor", and "Potential Stunting". Inclusion criteria were as follows: (1) studies with a population of children under five years of age, (2) studies that addressed risk factors for stunting, (3) studies of all types, and (4) articles published in English. Of the 200 articles, 98 met the inclusion criteria. This review categorised risk factors associated with stunting in children under five years of age into the Food cluster, Physical and social cluster, Health Services, and Housing. Underlying factors included food provisioning practices and access to health services and care. The underlying factors causing stunting are environmental, household health, and socioeconomic factors. This scoping review identified risk factors for childhood stunting, including child attributes, parental traits, the amount of food consumed by the child, child health, eating habits, access to health services, household and environmental health, and socioeconomic status. These factors are interrelated and influence each other. Therefore, paying attention to these factors is necessary to reduce the risk of stunting.